(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
It can be concluded that the task of popularizing a healthy lifestyle for future specialists of various professional profiles is complex and multicomponent. Its solution lies in the optimization of educational, circle and optional activities of the entire educational institution with the involvement of not only specialists in physical culture and sports and teachers of academic disciplines, but also psychologists, security specialists on the scale of not only the educational institution, but also the city, as well as the creation of a massive facts - advocacy campaign using a wide range of different means. The article analyzes the influence of physical education on the human psyche.